MEKANISME PELAYANAN PEJABAT NOTARIS DALAM PEMBUATAN AKTA DI MASA PANDEMI COVID-19 BERDASARKAN PERATURAN GUBERNUR NOMOR 53 TAHUN 2020 TENTANG PENERAPAN PROTOKOL KESEHATAN DALAM PENCEGAHAN DAN PENGENDALIAN COVID-19: (Studi Di Kantor Notaris Moh. Nur Kholis Muslim, SH., MKn.) - Hj. KHUSNUL HITAMINAH; Sisi Feronika (JUSTNESS - Jurnal Hukun dan Agama, 2022)
Abstract Notary officials are public officials who are authorized to make authentic deeds and have other authorities as referred to in this law. However, with the covid 19 pandemic, there are concerns in the service process of notaries in making authentic deeds of the transmission of covid, so there needs to be a new mechanism in providing services to their clients, one of which is Notary Moh. Nur Kholis Muslim, SH., MKn. Based on East Java Governor Regulation Number 53 of 2020 concerning Health Protocols. Notary Moh. Nur Kholis Muslim, SH., MKn. As a sample in this study by emphasizing the problems formulated in the problem formulation How is the service mechanism for making Authentic Deeds at the Notary Office Moh. Nur Kholis Muslim, SH., MKn. During the Covid 19 Pandemic? and What are the obstacles and strategies that can be done to provide excellent service to clients at the Notary Moh. Nur Kholis Muslim, SH., MKn. During the Covid 19 Pandemic? The purpose of this study was to determine the service mechanism at the Notary Moh. Nur Kholis Muslim, SH., MKn. In making an authentic deed during the covid 19 pandemic based on Governor Regulation Number 53 of 2020. This study uses an empirical juridical method, namely by approaching the problem through existing regulations and theories, then connecting it with field practice or facts that occur in the field according to the focus of the problem being studied or researched, where the object of this research is a direct approach to the Notary's office. Moh. Nur Kholis Muslim, SH., MKn. Paiton Probolinggo. Keywords: Notary Official, authority, authentic deed, covid 19 pandemic